UPAYA MENGATASI MELEMAHNYA PEMAHAMAN SISWA DAN KONSENTRASI BELAJAR SISWA PADA SDN 2 BRANTI RAYA - Febriyanti, Dewi (LPPM STKIP PGRI Bandar Lampung, 2019)
Various problems in elementary school students in high grades that arise due to environmental factors or peers, one of which is the lack of concentration of students when learning takes place which can cause various factors.The purpose of this study was (1) to get an overview of the level of concentration of children during learning (2) to obtain clear or detailed information about the factors that cause children to lack concentration while learning (3) to determine the causes and effects that will occur in children lack of concentration in studyingIn this study, researchers used a descriptive method. Quantitative methods can be interpreted as research methods based on positivism philosophy, data collection using research instruments, quantitative data analysis in order to test predetermined hypotheses.